The Effect of Yogurt Consumption with the Addition of Red Beet (Beta Vulgaris) on The Blood Pressure of Students in Carolina Dormitor - Wicaksana, Pramudya Satria; Setyaji, Diyan Yunanto; Lubijarsih, Maria Amrijati (Edu Dharma Journal :Jurnal penelitian dan pengabdian masyarakat, 2023)
Hypertension is a disease with a systolic blood pressure of more than 140 mmHg and a diastolic blood pressure of more than 90 mmHg. Yogurt and red beet (Beta vulgaris) have been known as foods containing potassium which is associated with lowering blood pressure. This study aims to determine the effect of giving yogurt with the addition of red beet on the blood pressure of college students in the Carolina Dormitory. This research was conducted with True Experiment Design, Pretest – Posttest with Control Group. The subjects used were 24 Carolina Dormitory students who were divided into 3 groups, including the control group (consuming yogurt), treatment group 1 (consuming yogurt and 50ml red beetroot), and treatment group 2 (consuming 100ml yogurt and red beetroot). The intervention was carried out in the afternoon for 6 days. Different test before and after intervention using paired t-test. Test the differences between groups using the One-Way ANOVA test. Potassium levels in each formulation were not significantly different (p0.05). Yogurt products with 100 ml of red beet have the highest potassium content. After receiving treatment for 6 days, all groups experienced a significant decrease in systolic and diastolic blood pressure (p0.05) compared to before treatment. Consumption of 100 ml of yogurt and 100 ml of red beetroot was able to reduce systolic blood pressure by 9.63 mmHg and diastolic blood pressure of 9.00 mmHg, but had no significant difference (p0.05) when compared to other groups. It can be concluded that the consumption of yogurt can lower blood pressure while the addition of beets to yogurt does not provide a significant difference in the effect of decreasing systolic and diastolic blood pressure.